Apa yang Harus Dipahami Perawat Tentang Pencegahan Nosokomial Terkait Multidrug-Resistant Organisms (MDROS)? - Rustiana Tasya Ariningpraja; Ika Yuni Widyawati; Endah Panca Lydia Fatma (Journal of Telenursing (JOTING), 2023)
This study aims to determine the important role of critical care nurses in preventing nosocomial infections caused by Multidrug-Resistant Organisms (MDROs). This review conducted a systematic search of electronic databases including PubMed, Scopus, CINAHL, Web of Science (WoS), and ScienceDirect, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. As a result of the study, Chlorhexidine baths, oral care, and environmental cleaning were identified as the most effective strategies for preventing MDROs in critical care settings and the impact of these strategies varied across studies. Caps containing alcohol to prevent bloodstream infections have also been shown to be effective. In conclusion, this review highlights the importance of implementing effective prevention strategies to reduce the incidence of MDROs in critical care settings. Critical care nurses must know the most effective strategies for preventing infections and implement them consistently. The findings of this review have important implications for clinical practice and policy development. Keywords: Intensive Care Unit; Nosocomial Infections, Multidrug-Resistant Organisms (MDROS), Critical Care Nursing